Changes of natriuresis and prediction of cardiovascular events in patients with type 2 diabetes and decompensated heart failure over therapy with sodium-glucose cotransporter 2 inhibitors and standard diuretic therapy - O. A. Abdullaev; A. G. Arutyunov; D. P. Vereshchak; E. V. Tavlueva; V. A. Konik; N. A. Bylova; D. V. Puzenko; N. P. Kulagina; I. R. Nurieva; T. V. Zanina; G. P. Arutyunov (Российский кардиологический журнал)
Aim. To evaluate the influence and changes of clinical and water-electrolyte parameters on the risk of cardiovascular events in the early period after decompensated heart failure (HF) in patients with type 2 diabetes (T2D), taking into account the influence of standard diuretic therapy and diuretic therapy in combination with sodium-glucose cotransporter 2 (SGLT-2) inhibitors.Material and methods. The study included 119 patients with type 2 diabetes and class III-IV HF. The duration of diagnosed HF at the time of enrollment was 6,9±1,1 years.Patients who met the inclusion criteria at the time of hospital admission were randomized into a group of standard therapy for decompensated HF (control group) and a group of combined diuretic therapy — loop diuretics + SGLT-2 inhibitors (main group).Results. Against the background of combined diuretic therapy with SGLT-2 inhibitors, a significant increase in diuresis was achieved, starting from the 2nd day: on day 2 — in the main group 1,342,83±159,74 ml/day and 1,250,17±134,53 ml/day in the control group (p=0,001, 95% confidence interval (CI)), on day 3, in the main — 1,895,17±249,95 ml/day, and in the control — 1,723,78±252,49 ml/day (p=0,004, 95% CI), on day 4, in the main — 2,382,50±246,29 ml/day and in the control — 2,124,83±2,86,44 ml/day (p=0,000002, 95% CI), on day 5, in the main — 2,785,50±282,38 ml/day and in the control group 2,458,39±273,36 ml/day (p<0,001, 95% CI).A comparison of the two groups showed a significant increase in natriuresis in the main group on day 5 (+111,1±10,54 ml) compared to the control (+75,53±15,01 ml, p<0,001, 95% CI). Extracellular fluid volume, determined by bioelectrical impedance analysis on day 5, decreased significantly higher when taking SGLT-2 inhibitors: in the main group the decrease was by 5,48±2,19 kg, in the control group — by 2,92±0,73 kg (p=0,02, 95% CI), On day 5, we revealed a significant inverse relationship between natriuresis level and extracellular fluid volume (r=0,217, p=0,018). Dapagliflozin (D), like empagliflozin (E), significantly and equally increases the level of natriuresis (D +108,25±13,56 mmol/day, p<0,001, E +112,52±8,50, p=0,00009) and reduces the extracellular fluid volume (D -5,05±1,46 kg, p<0,001, E -5,69±2,47, p<0,001) on day 5.Conclusion. In patients with type 2 diabetes hospitalized for decompensated HF, therapy with SGLT-2 inhibitors + loop diuretics lead to a significantly greater diuresis, natriuresis and a greater decrease in extracellular fluid volume. A significant inverse relationship was found between the extracellular fluid volume and natriuresis level on day 5. Dapagliflozin effectiveness in edema, assessed by natriuresis level on day of treatment, is identical to the empagliflozin.